If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(t + 3) = 2(5t + -3) Reorder the terms: -2(3 + t) = 2(5t + -3) (3 * -2 + t * -2) = 2(5t + -3) (-6 + -2t) = 2(5t + -3) Reorder the terms: -6 + -2t = 2(-3 + 5t) -6 + -2t = (-3 * 2 + 5t * 2) -6 + -2t = (-6 + 10t) Add '6' to each side of the equation. -6 + 6 + -2t = -6 + 6 + 10t Combine like terms: -6 + 6 = 0 0 + -2t = -6 + 6 + 10t -2t = -6 + 6 + 10t Combine like terms: -6 + 6 = 0 -2t = 0 + 10t -2t = 10t Solving -2t = 10t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-10t' to each side of the equation. -2t + -10t = 10t + -10t Combine like terms: -2t + -10t = -12t -12t = 10t + -10t Combine like terms: 10t + -10t = 0 -12t = 0 Divide each side by '-12'. t = 0 Simplifying t = 0
| 31/2-31/4x=-15/8 | | 2x+13=3y | | 4756505-2896112*1600=x | | 2x+13=3t | | m/200 | | 204=2(8x+5)+6(2x+9) | | 5x+2x+8=180 | | -8y-1=7y-8 | | 6(-x-4)=2x+8 | | -4=r/29 | | -19-15d+22d=4.4 | | 4/x+2=7/2x-3 | | -3x-2=5x-58 | | 6x+4(2x-11)=26 | | 17=2(8x+5)+6(2x+9) | | -9+2wx+x=y | | -16x^2-22x+112=0 | | 2g+2(-7+5g)=1-g | | 3n+17+4n+16=180 | | 7x+4(2x-12)=27 | | n+10=-4 | | 7(8v+7)-5(6v-8)=245 | | 12=-6(n-8) | | 1/4+4x/5=12/20 | | 7(8v+7)+5(6v-8)=245 | | (X^2)-8x+137=0 | | -4y-7=3y-8 | | y+2x+60=180 | | 4/2+6t=2 | | 5/4-3/16 | | 4x-16=3x-7 | | 4y-10=3x |